Management of fruit and vegetable waste into ecoenzyme in Drien Rampak Village, West Aceh Regency - Agustinur Agustinur; Dewi Junita; Sumeinika Fitria Lizmah; Chairul Rizal; Muhammad Afrillah; Vina Maulidia (University of Merdeka Malang, 2024)
The accumulation of waste in public areas of Drien Rampak Village remains an unresolved issue. The growing population has led to increased consumption and waste production. Currently, there is no waste management mechanism capable of addressing this problem effectively. The waste is predominantly household waste, such as organic fruit and vegetable residues. This activity aimed to provide training to the PKK women’s group in Drien Rampak Village on making ecoenzymes as a solution for managing organic waste. The implementation included training and hands-on assistance. The stages of the activity were as follows: coordination with partners, education on waste management, ecoenzyme-making training, fermentation process, and ecoenzyme harvesting. The activity produced 100 liters of ecoenzyme using 30 kg of fruit and vegetable residues. Based on pre-test and post-test questionnaire results, significant improvements were observed in participants' attitudes, knowledge, and skills in managing household organic waste. The highest improvement was in attitudes (16.84-point difference), followed by skills (13.11-point difference) and knowledge (5.49-point difference).